Critical systemic risk sources in global lithium-ion battery supply networks: Static and dynamic network perspectives. (March 2023) - Hu, Xiaoqian; Wang, Chao; Lim, Ming K.; Chen, Wei-Qiang; Teng, Limin; Wang, Peng; Wang, Heming; Zhang, Chao; Yao, Cuiyou; Ghadimi, Pezhman
Abstract: Due to the indispensable role of electric vehicles (EVs) in achieving carbon neutrality, lithium-ion batteries (LIBs) for EVs have attracted considerable attention in the context of a widely distributed raw material supply and cross-border LIB production. Most previous studies have focused on only one specific LIB-related commodity supply, ignoring the intricate dependent relationships among mineral resources, intermediate components, and finished products. To fill this gap, this study employs a multilayer network model to construct the global EV-LIB supply network from 1990 to 2020 and explores critical risk sources from static and dynamic network perspectives. From the static perspective, the results based on the MultiRank algorithm reveal the critical position of countries, which are covered by single-layer-based indicators. The EV-LIB industry is shifting from upstream mineral resources to intermediate components and finished products (EV-LIBs and anodes). From the dynamic perspective, the impacts of risk sources and their risk transmission paths are revealed by the proposed dynamic shock propagation models under two realistic scenarios, i.e., supply restrictions on a specific commodity and blocked export channels. Some unremarkable shocks to a specific upstream commodity are revealed to have a substantial influence on downstream processes. Different effects of improving a country's anti-risk capacity on strengthening the robustness of the trade system are shown. The findings provide anti-risk support for policymakers seeking to hedge supply risks, adjust industrial planning, and ensure industrial safety. Graphical abstract: Image 1 Highlights: The global EV-LIB supply network is explored based on a multilayer network model. The influence of countries and commodities is assessed in the multilayer network. The impacts of supply restrictions are assessed based on shock propagation models. The sensitivity of fragility to a country's anti-risk capacity has three patterns. Hidden risks caused by supply restrictions imposed by core countries are revealed. Abstract : A synopsis of the GELSN is provided in terms of topological characteristics in Subsection 3.1, and the detailed results are presented in Appendix A4. Overall, the GELSN grows steadily. The import competition and export monopolization of EV-LIBs are higher than those of other commodities. From 1990 to 2020, an increasing amount of trade value for each commodity in the GELSN was controlled by a few countries. Specifically, the heterogeneity of the EV-LIB trade is higher than that of most other commodities. The results show a stronger association between the single-layer network of intermediate components (cathode and anode) and that of finished products (EV-LIBs). Therefore, it is assumed that these trade markets will be highly synchronized under shocks.